HISTORICAL AND THEOLOGICAL ANALYSIS OF «THE PASTORAL MESSAGE OF METROPOLITAN JOSYP SLIPYI ON THE OCCASION OF THE ASCENDING OF THE HOLY SPIRIT IN 1947» - MARTYNIUK, Bishop Theodore (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2023)
The article examines the pastoral message of Metropolitan Josyp Slipyi from captivity to the faithful people on the occasion of the Ascending of the Holy Spirit in 1947. It was found out that after the arrest of the Galician Metropolitan and the unfair trial sentence, Josyp Slipyi found a way in the penal servitude, risking an increase in the punishment, to support the spirit of his flock, his faithful, wrote the Message from Exile, which differed in numerous censuses. Unfortunately, the text of the messages from 1948 is unknown because they have yet to be preserved. However, one letter, written by the bishop-convict in 1947 on the feast of the Sending of the Holy Spirit, became known only at the end of 2003, when it was found hidden in the Univ Lavra. The place and conditions of writing the message, its purpose and content are revealed. Josyp Slipyi sets himself the goal that, despite the thousands of kilometres that separate him from the metropolitan settlement in Lviv, through the message to be present in the midst of his faithful and comfort them in their suffering. It is emphasized that the message aims to strengthen the faith of the suffering people; however, writing it and entrusting it to the faithful, the Metropolitan of Galicia himself is looking for strength and consolation: «Accept, dear ones, this word of instruction and comfort, just as I, when writing it, found relief in grief». It has been proven that Lviv Archbishop Yosyp, enslaved and tortured by the Soviet regime as a tireless shepherd, used every opportunity to appeal to his faithful and the clergy. The difficult circumstances of captivity did not allow him to do this often. However, he looked for opportunities to write messages. The message for the Feast of the Sending of the Holy Spirit is relevant today when the Ukrainian people are fighting against the Russian aggressor. This same aggressor tried to destroy Metropolitan Yosyp. However, the long-term prisoner of the Soviet camps did not break down and became an example of courage and resilience for millions of Ukrainians.